Anti-TNF Therapy and the Risk of Herpes Zoster Among Patients With Inflammatory Bowel Disease. Issue 2 (17th May 2021) - Santella, Christina; Bitton, Alain; Filliter, Christopher; Bessissow, Talat; Vutcovici, Maria; Lakatos, Peter L; Brassard, Paul
Abstract: Background: The specific contribution of anti-TNF therapy to the onset of herpes zoster (HZ) in patients with inflammatory bowel disease (IBD) remains uncertain. Thus, the purpose of this nested case-control study was to explore whether the use of anti-TNF therapy is associated with an increased risk of HZ. Methods: Using the Regie de l'Assurance Maladie du Québec, we identified incident cases of IBD between 1998 and 2015. We matched IBD cases of HZ with up to 10 IBD HZ-free controls on year of cohort entry and follow-up. Current use was defined as a prescription for anti-TNF therapy 60 days before the index date, with nonuse as the comparator. We conducted conditional logistic regression to estimate odds ratios (ORs) with 95% confidence intervals (CIs), adjusting for potential confounders. Results: The cohort consisted of 15, 454 incident IBD patients. Over an average follow-up of 5.0 years, 824 patients were diagnosed with HZ (incidence of 9.3 per 1000 person-years). Relative to nonuse, current use of anti-TNF therapy was associated with an overall increased risk of HZ (OR, 1.5; 95% CI, 1.1–2.1). The risk was increased among those older than 50 years (OR, 2.1; 95% CI, 1.2–3.6) and those additionally using steroids and immunosuppressants (OR, 4.1; 95% CI, 2.3–7.2). Conclusions: Use of anti-TNF therapy was associated with an increased risk of HZ among patients with IBD, particularly among those older than 50 years and those on combination therapy. Prevention strategies for HZ ought to be considered for younger IBD patients commencing treatment.